Comparative Diagnostic Value of Dengue Infection Using ELFA and Two Commercial Immuno-Chromatography Tests - Nugraha, Jusak; Luminto, Dian; Saputri, Agatha Efrad (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Dengue Virus (DEN-V) can lead to a broad spectrum of clinical presentations, from mild symptoms to mortality. Based on the presence of antibodies, dengue infection is categorized into primary and secondary dengue. Early diagnosis is crucial for effective treatment of DEN-V infection. Non-Structural Antigen 1 (NS1) and dengue antibodies like immunoglobulin M (IgM) and immunoglobulin G (IgG) anti-dengue are standard assays used for dengue diagnosis. Various immunoassay methods, including Enzyme-Linked Fluorescent Assay (ELFA) and Immuno-Chromatographic Tests (ICT), are employed to detect these antigens and antibodies. This study aimed to compare the diagnostic value between ELFA and two commercial ICTs for detecting NS1 antigen, IgM/IgG anti-dengue. Seventy suspected dengue patients with fever lasting two to seven days at Premier Hospital, Surabaya were enrolled in this study. Blood serum samples from the individuals were tested for NS1 antigen and IgM/IgG anti-dengue using VIDAS® and two commercial ICTs (Boson and SD Bioline). The sensitivity of NS1 antigen assays using ELFA and two ICTs was calculated, as well as the agreement rate between ELFA and both ICTs. ELFA demonstrated high sensitivity (77.97%) for NS1 antigen detection in diagnosing dengue infection compared to two ICTs (76.27% and 45.45%). Using an automated system in ELFA can offer more excellent diagnostic value and objective results and determine the cut-off ratio of IgM/IgG antibodies. All of this comes at a cost comparable to ICT.